Enamel glaze with photocatalytic function, preparation process and application thereof

CN118479734BActive Publication Date: 2026-10-30QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410628346.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2026-10-30
Estimated Expiration
2044-05-21

AI Technical Summary

Technical Problem

[0004]目前,标识基体通常使用不锈钢材质,至今尚未有报道关于具有较好光催化功能的复合结构搪瓷标识

Benefits of technology

(1)新型光催化搪瓷制品采用釉料与CuO@TiO2复合设计理念,兼具了两者优势。搪瓷釉料具有良好的耐腐蚀性和耐磨损性,CuO@TiO2作为一种新型光催化剂,具有优异的光催化活性,两种材料复合赋予了标识结构与功能双重特性,拓宽了气瓶标识应用领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118479734B_ABST
    Figure CN118479734B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of enamel materials, and relates to an enamel glaze with photocatalytic function, a preparation process and application. The present application prepares CuO@TiO2, mixes the glaze with CuO@TiO2 powder sufficiently, obtains a new type of enamel glaze, applies the above-mentioned enamel glaze on a processed identification substrate, dries and sinteres to obtain an enamel identification product. The method adopts the design principle of the composite structure of the enamel glaze and CuO@TiO2, the enamel glaze has good corrosion resistance and wear resistance, CuO@TiO2 has excellent photocatalytic activity, and the combination of the two materials endows the identification structure with double excellent characteristics of structure and function. The prepared new type of photocatalytic identification product can play the roles of high enamel strength, stable structure and effective degradation of pollutants by photocatalysts, effectively reduces external damage, and prolongs the service life of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of enamel material technology, and relates to a photocatalytic enamel glaze, its preparation process, and its application. Background Technology

[0002] Solar energy is a widely available, pollution-free renewable energy source. With continuous technological advancements and cost reductions, the scope and scale of solar energy utilization will continue to expand, thus attracting increasing attention to photocatalysis technology. Photocatalysis is a technology that utilizes light energy to excite catalyst activity. It is based on the interaction between photons and the catalyst surface when light irradiates the surface, converting the photon energy into electrons and holes, forming photogenerated electron-hole pairs, and promoting chemical reactions. These photogenerated electrons and holes possess certain redox capabilities; under light irradiation, they can react with substances adsorbed on the catalyst surface, transforming them into harmless or low-toxic substances.

[0003] Titanium dioxide (TiO2) exhibits excellent photocatalytic performance, effectively absorbing visible and ultraviolet light and utilizing light energy to convert harmful substances into harmless products, thus achieving the degradation and removal of pollutants. Furthermore, TiO2 demonstrates strong stability, exhibiting good resistance to acids, alkalis, oxidants, and high temperatures, and can withstand harsh conditions such as high temperatures and chemical corrosion, maintaining its catalytic activity for a long time. It is commonly available in powder form, easily prepared into thin films or coated onto supports, making the process simple. CuO, as a p-type semiconductor, is combined with TiO2 to form a pn heterostructure copper oxide / titanium dioxide composite material (CuO@TiO2), which effectively separates photogenerated electrons and holes, hindering their recombination and significantly improving electron mobility. The CuO@TiO2 composite material is a nanocomposite material with excellent photocatalytic performance. The TiO2 bandgap is located in the ultraviolet region; when CuO@TiO2 is exposed to ultraviolet light, the ultraviolet light provides energy to excite TiO2 valence band electrons to the conduction band, forming electron-hole pairs. Excited electrons migrate from the conduction band of TiO2 to the conduction band of CuO, forming electrons with high reducing power. The key to this process lies in the interface between CuO and TiO2; the two components exhibit energy level matching, and CuO, as a p-type semiconductor, allows electrons to migrate from TiO2 to CuO, forming separable electron-hole pairs. The excited electrons then react with oxygen or organic pollutants in the solution, resulting in reduction. Typical reduction reactions include the reduction of oxygen molecules to superoxide ions (O2). -This process involves the partial reduction of organic pollutants. Simultaneously, holes react with hydroxide ions, undergoing oxidation. These redox reactions effectively degrade organic pollutants into smaller, safer, and more stable substances. On the surface of the CuO@TiO2 composite material, these redox reactions promote the degradation of organic pollutants, converting them into harmless substances, while simultaneously producing relatively stable byproducts such as water and carbon dioxide.

[0004] Currently, stainless steel is commonly used as the substrate for signage, and there are no reports to date on composite enamel signage with good photocatalytic function. The novel photocatalytic signage, however, uses a composite method of photocatalyst and enamel to form a photocatalytic enamel sign. When irradiated by a light source, the photocatalytic components exhibit photocatalytic activity, effectively degrading organic pollutants on its surface and effectively isolating corrosive gases from the stainless steel substrate, thus improving the signage's corrosion resistance. Summary of the Invention

[0005] This invention provides a photocatalytic enamel glaze, its preparation process, and its application. The method employs a composite structure of enamel glaze and CuO@TiO2, resulting in an enamel coating that combines high strength, corrosion resistance, and photocatalytic functionality. This endows the markings with photocatalytic properties, improves the strength of the new markings (enamel products), and extends the service life of the marking products.

[0006] To achieve the above objectives, the present invention adopts the following solution: A process for preparing a photocatalytic enamel glaze includes the following steps: (1) Preparation of CuO@TiO2: Add 0.05 mol / L CuSO4·5H2O solution to a beaker, and add titanium dioxide at the same time. Stir at room temperature to obtain solution A. Add 0.1 mol / L NaOH solution dropwise to solution A, stirring continuously during the dropwise addition. After completion, transfer the above solution to a hydrothermal reactor for hydrothermal treatment for 12 h, then wash with water and filter. Dry at 50 ℃ and grind into fine powder to obtain CuO@TiO2 powder. (2) Place the glaze in a mortar, add ultrapure water, and grind continuously until it becomes a paste; (3) Then add the CuO@TiO2 powder obtained in step (1) to the slurry glaze and mix it thoroughly to obtain enamel glaze.

[0007] Preferably, in step (1), the molar ratio of titanium dioxide to CuSO4·5H2O is 9:1; and the volume ratio of CuSO4·5H2O solution to NaOH solution is 1:1.

[0008] Preferably, in step (2), the mass ratio of glaze to ultrapure water is 20~60:80~40.

[0009] Preferably, the mass fraction of CuO@TiO2 powder in step (3) is 5~40 wt.%.

[0010] The present invention also includes enamel glaze obtained by the above preparation process and the application of the enamel glaze in the preparation of corrosion-resistant and photocatalytic products.

[0011] In addition, the present invention also provides a process for preparing enamel products, the steps of which are as follows: ① The above-mentioned enamel glaze is applied to a stainless steel substrate to obtain sample A. Sample A is then dried in a drying oven at 40-80℃. The substrate undergoes pretreatment, and the pretreatment steps are as follows: S1: Place the substrate in a beaker, add acetone solvent to the beaker, and ultrasonically clean it; S2: Rinse the acetone-cleaned substrate with deionized water, and then immerse it in glacial acetic acid solvent for treatment; S3: Place the acid-washed matrix obtained in S2 into anhydrous ethanol for ultrasonic cleaning, and then dry it for later use. ② Place the dried sample A into a resistance furnace and heat it to 750 ℃~850 ℃ at a rate of 5-15℃ / min. Sinter the sample at 750℃~850℃ to obtain enamel products.

[0012] Preferably, the substrate dimensions in step ① are 20×50×0.3 mm, and the substrate material is stainless steel.

[0013] Preferably, in step ①, acetone in S1 is of analytical grade; and glacial acetic acid in S2 is of analytical grade.

[0014] Preferably, in step ①, the ultrasonic cleaning time in S1 is 5-30 min, the soaking time in S2 is 5-24 h, and the ultrasonic cleaning time in S3 is 5-20 min.

[0015] Preferably, the sintering time in step ② is 5~30 min.

[0016] Preferably, the heating rate in step ② is 10℃ / min, and the sintering temperature is 800℃.

[0017] The present invention also includes enamel products obtained by the above-described preparation process.

[0018] The enamel glaze and CuO@TiO2 composite coating enamel products provided by this invention have the following advantages: (1) The new photocatalytic enamel products adopt the composite design concept of enamel and CuO@TiO2, which combines the advantages of both. Enamel enamel has good corrosion resistance and wear resistance, while CuO@TiO2, as a new type of photocatalyst, has excellent photocatalytic activity. The combination of the two materials gives the marking structure and function dual characteristics, which broadens the application field of gas cylinder marking.

[0019] (2) This invention provides a solution to effectively extend the service life of labels. In harsh environments, traditional gas cylinder labels are easily corroded by environmental pollutants or mechanical collisions, leading to corrosion or damage. The novel photocatalytic functional label prepared by this invention can leverage the high strength, structural stability, and effective degradation of pollutants of enamel, effectively reducing external damage and extending the service life of the label. Attached Figure Description

[0020] Figure 1 SEM image of the microstructure of the enamel surface; Figure 2 XRD pattern of photocatalytic enamel; Figure 3 Image of an enamel product demonstrating photocatalytic effect; Figure 4 The photocatalytic degradation effect on novel enamel products; Figure 5 The photocatalytic degradation rate of novel enamel products. Detailed Implementation

[0021] The present invention will be further described below with reference to specific embodiments, and the advantages and features of the present invention will become clearer with the description. However, the embodiments are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art should understand that modifications or substitutions can be made to the details and form of the technical solutions of the present invention without departing from the spirit and scope of the present invention, but all such modifications and substitutions fall within the protection scope of the present invention.

[0022] Example 1 A photocatalytic enamel glaze and its preparation process The steps are as follows: (1) Preparation of CuO@TiO2: Add 0.05 mol / L CuSO4·5H2O solution to a beaker, and add titanium dioxide at the same time. The molar ratio of titanium dioxide to CuSO4·5H2O is 9:1. Stir at room temperature to obtain solution A. Add 0.1 mol / L NaOH solution dropwise to solution A with an equal volume of copper sulfate solution, stirring continuously during the dropwise addition. After completion, transfer the solution to a hydrothermal reactor and hydrothermally heat for 12 h. Then wash with water several times and filter. After drying at 50 ℃, grind continuously into fine powder to obtain sample CuO@TiO2. (2) Place the glaze in a mortar, add ultrapure water, the mass ratio of glaze to ultrapure water is 50:50, and grind continuously until the sample is in the form of a paste; (3) Then add 30wt.% CuO@TiO2 powder obtained in step (1) to the slurry glaze and mix it thoroughly to obtain enamel glaze.

[0023] An enamel product and its manufacturing process The steps are as follows: ① The above-mentioned enamel glaze was applied to a 20×50×0.3 mm stainless steel substrate to obtain sample A. Sample A was then placed in a 50℃ drying oven and dried for 15 min. The substrate underwent pretreatment, and the pretreatment steps are as follows: S1: Place the substrate in a beaker, add acetone solvent to the beaker, and ultrasonically clean for 5 minutes; S2: Rinse the acetone-cleaned matrix with deionized water, and then soak it in glacial acetic acid solvent for 5 hours; S3: Place the acid-washed substrate obtained in S2 into anhydrous ethanol for ultrasonic cleaning for 5 min, and dry it for later use. This method is a wet coating method, which can make the sample coating uniform and smooth. ② The dried sample A was placed in a resistance furnace and heated to 750 °C at a rate of 10 °C / min. Sintering was then carried out at 750 °C for 30 min to obtain the enamel product. The SEM image of the enamel surface microstructure is shown below. Figure 1 As shown, the photocatalytic material and glaze are well bonded after calcination, and catalyst particles are embedded in the surface structure.

[0024] Example 2 A photocatalytic enamel glaze and its preparation process The steps are as follows: (1) Preparation of CuO@TiO2: Add 0.05 mol / L CuSO4·5H2O solution to a beaker, and add titanium dioxide at the same time. The molar ratio of titanium dioxide to CuSO4·5H2O is 9:1. Stir at room temperature to obtain solution A. Add 0.1 mol / L NaOH solution dropwise to solution A with an equal volume of copper sulfate solution, stirring continuously during the dropwise addition. After completion, transfer the solution to a hydrothermal reactor and hydrothermally heat for 12 h. Then wash with water several times and filter. After drying at 50 ℃, grind continuously into fine powder to obtain sample CuO@TiO2. (2) Place the glaze in a mortar, add ultrapure water, the mass ratio of glaze to ultrapure water is 50:50, and grind continuously until the sample is in the form of a paste; (3) Then add 20.wt% CuO@TiO2 powder obtained in step (1) to the slurry glaze and mix it thoroughly to obtain enamel glaze.

[0025] An enamel product and its manufacturing process The steps are as follows: ① The above-mentioned enamel glaze was applied to a 20×50×0.3 mm stainless steel substrate to obtain sample A. Sample A was then placed in a 50℃ drying oven and dried for 20 min. The substrate underwent pretreatment, and the pretreatment steps are as follows: S1: Place the substrate in a beaker, add acetone solvent to the beaker, and ultrasonically clean for 30 min; S2: Rinse the acetone-cleaned matrix with deionized water, and then soak it in glacial acetic acid solvent for 24 hours; S3: Place the acid-washed matrix obtained in S2 into anhydrous ethanol for ultrasonic cleaning for 20 min, and then dry it for later use. ② The dried sample A was placed in a resistance furnace and heated to 820 °C at a rate of 12 °C / min. It was then sintered at 820 °C for 5 min to obtain the enamel product. The XRD pattern of the sample is shown below. Figure 2 As shown, the enamel structure contains titanium dioxide and copper oxide phases, which achieve good composite with the enamel material.

[0026] Example 3 A photocatalytic enamel glaze and its preparation process The steps are as follows: (1) Preparation of CuO@TiO2: Add 0.05 mol / L CuSO4·5H2O solution to a beaker, and add titanium dioxide at the same time. The molar ratio of titanium dioxide to CuSO4·5H2O is 9:1. Stir at room temperature to obtain solution A. Add 0.1 mol / L NaOH solution dropwise to solution A with an equal volume of copper sulfate solution, stirring continuously during the dropwise addition. After completion, transfer the solution to a hydrothermal reactor and hydrothermally heat for 12 h. Then wash with water several times and filter. After drying at 50 ℃, grind continuously into fine powder to obtain sample CuO@TiO2. (2) Place the glaze in a mortar, add ultrapure water, the mass ratio of glaze to ultrapure water is 30:70, and grind continuously until the sample is in the form of a paste; (3) Then add 10.wt% CuO@TiO2 powder obtained in step (1) to the slurry glaze and mix it thoroughly to obtain enamel glaze.

[0027] An enamel product and its manufacturing process The steps are as follows: ① The above-mentioned enamel glaze was applied to a 20×50×0.3 mm stainless steel substrate to obtain sample A. Sample A was then placed in a 40 ℃ drying oven for 30 min. The substrate underwent pretreatment, and the pretreatment steps are as follows: S1: Place the substrate in a beaker, add acetone solvent to the beaker, and ultrasonically clean for 10 min; S2: Rinse the acetone-cleaned matrix with deionized water, and then soak it in glacial acetic acid solvent for 12 hours; S3: Place the acid-washed matrix obtained in S2 into anhydrous ethanol for ultrasonic cleaning for 10 min, and then dry it for later use. ② The dried sample A was placed in a resistance furnace and heated to 760 °C at a rate of 8 °C / min. Sintering was then carried out at 760 °C for 15 min to obtain the enamel product. The photocatalyst and glaze bonded well, resulting in a smooth and intact surface. Figure 3 As shown.

[0028] Example 4 A photocatalytic enamel glaze and its preparation process The steps are as follows: (1) Preparation of CuO@TiO2: Add 0.05 mol / L CuSO4·5H2O solution to a beaker, and add titanium dioxide at the same time. The molar ratio of titanium dioxide to CuSO4·5H2O is 9:1. Stir at room temperature to obtain solution A. Add 0.1 mol / L NaOH solution dropwise to solution A with an equal volume of copper sulfate solution, stirring continuously during the dropwise addition. After completion, transfer the solution to a hydrothermal reactor and hydrothermally heat for 12 h. Then wash with water several times and filter. After drying at 50 ℃, grind continuously into fine powder to obtain sample CuO@TiO2. (2) Place the glaze in a mortar, add ultrapure water, the mass ratio of glaze to ultrapure water is 40:60, and grind continuously until the sample is in the form of a paste; (3) Then add 20.wt% CuO@TiO2 powder obtained in step (1) to the slurry glaze and mix it thoroughly to obtain enamel glaze.

[0029] An enamel product and its manufacturing process The steps are as follows: ① The above-mentioned enamel glaze was applied to a 20×50×0.3 mm stainless steel substrate to obtain sample A. Sample A was then placed in a 60 ℃ drying oven for 5 min. The substrate underwent pretreatment, and the pretreatment steps are as follows: S1: Place the substrate in a beaker, add acetone solvent to the beaker, and ultrasonically clean for 10 min; S2: Rinse the acetone-cleaned matrix with deionized water, and then soak it in glacial acetic acid solvent for 24 hours; S3: Place the acid-washed matrix obtained in S2 into anhydrous ethanol for ultrasonic cleaning for 10 min, and then dry it for later use. ② Place the dried sample A into a resistance furnace and heat it to 800 ℃ at a rate of 10℃ / min. Sinter it at 800℃ for 5 min to obtain the enamel product.

[0030] Comparative Example 1 A manufacturing process for enamel products Place the glaze in a mortar, add ultrapure water, and the mass ratio of glaze to ultrapure water is 40:60. Grind continuously until the sample is in a slurry state to obtain glaze A. Apply glaze A directly to a 20×50×0.3 mm stainless steel substrate. The remaining steps are the same as the preparation process of the enamel product in Example 4.

[0031] Experimental Example 1 Evaluation of photocatalytic performance of enamel products.

[0032] The enamel glaze samples obtained in Example 4 and Comparative Example 1 were added to 100 mL of methylene blue solution (30 mg / L), stirred, and then dark-treated for 60 min. The photocatalytic effect of the products was characterized, and it was found that the catalyst endowed the samples with stronger photocatalytic properties, such as... Figure 4 As shown. Using UV-Vis spectrophotometry, the enamel glaze of Example 4 showed a methylene blue degradation rate of 79.42% within 100 minutes, while the enamel glaze of Comparative Example 1 under the same conditions only showed a degradation rate of 45.82%. Figure 5 As shown.

Claims

1. A preparation process for an enamel glaze with photocatalytic function, characterized in that, The preparation process includes the following steps: (1) Preparation of CuO@TiO2: Add 0.05 mol / L CuSO4·5H2O solution to a beaker, and add titanium dioxide at the same time. Stir at room temperature to obtain solution A. Add 0.1 mol / L NaOH solution dropwise to solution A, stirring continuously during the addition. After completion, transfer the solution to a hydrothermal reactor for hydrothermal treatment for 12 h, then wash with water and filter. Dry at 50 ℃ and grind into fine powder to obtain CuO@TiO2 powder. (2) Place the glaze in a mortar, add ultrapure water, and grind continuously until it becomes a paste; (3) Then add the CuO@TiO2 powder obtained in step (1) to the slurry glaze and mix it thoroughly to obtain enamel glaze.

2. The preparation process according to claim 1, characterized in that, In step (1), the molar ratio of titanium dioxide to CuSO4·5H2O solution is 9:1; the volume ratio of CuSO4·5H2O solution to NaOH solution is 1:1; and in step (2), the mass ratio of glaze to ultrapure water is 20~60:80~40.

3. The preparation process according to claim 1, characterized in that, In step (3), the mass fraction of CuO@TiO2 powder is 5~40 wt.%.

4. The enamel glaze obtained by the preparation process according to any one of claims 1-3.

5. The application of the enamel glaze as described in claim 4 in the preparation of corrosion-resistant and photocatalytic products.

6. A manufacturing process for enamel products, characterized in that, Includes the following steps: ① The enamel glaze as described in claim 4 is applied to the marking substrate to obtain sample A. Sample A is then dried in a drying oven at 40-80℃. The substrate undergoes pretreatment, and the pretreatment steps are as follows: S1: Place the substrate in a beaker, add acetone solvent to the beaker, and ultrasonically clean it; S2: Rinse the acetone-cleaned substrate with deionized water, and then immerse it in glacial acetic acid solvent for soaking treatment; S3: Place the acid-washed matrix obtained in S2 into anhydrous ethanol for ultrasonic cleaning, and then dry it for later use. ② Place the dried sample A into a resistance furnace and heat it to 750 ℃~850 ℃ at a rate of 5-15℃ / min. Sinter the sample at 750℃~850℃ to obtain enamel products.

7. The preparation process according to claim 6, characterized in that, In step ①, the substrate size is 20×50×0.3 mm, and the substrate material is stainless steel; in step ①, S1, the acetone is analytical grade, and the ultrasonic cleaning time is 5~30 min; in S2, the soaking time is 5-24 h, and the glacial acetic acid in S2 is analytical grade; in S3, the ultrasonic cleaning time is 5-20 min.

8. The preparation process according to claim 6, characterized in that, In step ②, the heating rate is 10℃ / min and the sintering temperature is 800℃.

9. The preparation process according to claim 6, characterized in that, The sintering time in step ② is 5~30 min.

10. The enamel article obtained by the preparation process according to any one of claims 6-9.

Citation Information

Patent Citations

  • Cu2O / TiO2 composite photocatalysis material and production method thereof

    CN106466604A

  • Alumina ceramic-wear resistant steel composite material and preparation method thereof

    CN109455935A